The Effect of Using Quizizz Application in Learning with Science Education for Sustainable Development Approach on Students' Critical Thinking Ability - Ramadhan*, Nurul Huda; Fadly, Wirawan (Jurnal IPA & Pembelajaran IPA, 2024)
In TIMSS 2019, Indonesia is ranked 56 out of 58 countries, so teachers need to know the criteria for interactive media, learning media that must be used by teachers so that they are happy and acceptable to students. Quizizz is one of the interactive media chosen by teachers as a medium for learning because it is based on games and technology. The purpose of this study was to determine the effect of using Quizizz media on students' critical thinking skills in science subjects This research method uses a quantitative approach, because the data presented is in the form of numbers with a weak-experimental research design. The number of samples in this study was 64 students, who were divided into experimental groups and control groups. The instruments given are test sheets and satisfaction questionnaire sheets. Based on the results of research that has been carried out pretest on the control class and experimental class obtained an effect convention value of 0.19 which can be said there is no significant difference between the control class and the experimental class and after being given postest treatment obtained by the control class and experimental class the effect convention value This can be said to be a significant difference between the control class and the experimental class. So it can be concluded that there is a positive influence on the use of Quizizz on science learning with the SESD approach on students' critical thinking skills